Pola asuh orang tua terhadap adiksi penggunaan gawai pada anak usia sekolah: Literature review - Tri Cahyo Sepdianto; Faisal Agus Mustofa; Andi Hayyun Abiddin (Holistik Jurnal Kesehatan, 2022)
Background: In this modern era, technological developments involving gadgets and gadgets are growing very rapidly. As adults, they already understand the use of the device and can control it themselves, but as children, they still tend to play, which has an addictive or addictive effect. Parenting patterns are very necessary to control and supervise the use of gadgets or gadgets in children.Purpose: To determine the parenting pattern of the addiction to the use of gadgets in school-age children.Method: Using a literature review study through a PEOS search strategy in one database, namely Google Scholar.Results: There were 5 studies that met the inclusion criteria including using a cross-sectional, quasi-experimental design, and observational analytic; studies published between 2017-2022. Based on the results of the analysis, it was found that permissive parenting contributed to higher levels of gadget addiction in elementary school students. Democratic parenting affects the level of gadget addiction in elementary school students. Permissive parenting shows a high level of dependence among elementary school children.Conclusion: Parenting patterns affect the level of device addiction in elementary school children.Keywords: Parenting Style; Gadgets; Elementary school-age childrenPendahuluan: Di era modern ini, perkembangan teknologi yang melibatkan gadget dan gadget berkembang sangat pesat. Sebagai orang dewasa, mereka sudah memahami penggunaan perangkat dan dapat mengontrolnya sendiri, tetapi sebagai anak-anak, mereka masih cenderung bermain, yang efeknya menimbulkan kecanduan atau efek kecanduan. Pola asuh orang tua sangat diperlukan untuk mengontrol dan mengawasi penggunaan gawai atau gadget pada anak.Tujuan: Untuk mengetahui pola asuh orang tua terhadap adiksi penggunaan gawai pada anak usia sekolah.Metode: Menggunakan literature review study melalui strategi pencarian PEOS pada satu data base yaitu google scholar.Hasil: Didapatkan 5 studi yang sesuai dengan kriteria inklusi diantaranya menggunakan desain cross-sectional, kuasi-eksperimental, observational analitik. studi yang dipublikasikan antara tahun 2017-2022. Berdasarkan hasil analisis didaptakn abahwa pola asuh permisif berkontribusi pada tingkat kecanduan gadget yang lebih tinggi pada siswa sekolah dasar. Pola asuh demokratis mempengaruhi tingkat kecanduan gadget pada siswa sekolah dasar. Pola asuh permisif menunjukkan tingkat ketergantungan yang tinggi di antara anak-anak sekolah dasar.Simpulan: Pola asuh orang tua mempengaruhi tingkat kecanduan perangkat pada anak sekolah dasar.